Microstructure and characterization of Ag1−xLixNbO3 ceramics. Issue 3 (15th February 2016) - Niewiadomski, A.; Kajewski, D.; Kania, A.; Balin, K.; Miga, S.; Pawlik, M.; Koperski, J.
Abstract: Silver–lithium niobate, Ag1− x Li x NbO3, is a promising candidate for lead-free piezoelectrics. Ceramic samples for x equal 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.08 and 0.1 were synthesized by solid state reaction. Room temperature X-ray studies indicate that all samples consist mainly of perovskite phase. Only small amounts of secondary phases, namely Ag2 Nb4 O11, Ag and LiNbO3, appear. For x ≈0.06 the orthorhombic–rhombohedral morphotropic phase boundary is observed. Excellent piezoelectric properties, recently reported for x >0.1, may be the result of proximity of morphotropic phase boundary. Scanning electron microscopy and secondary ion mass spectroscopy investigations suggest that the secondary phases occur chiefly at the grain boundaries. Dielectric measurements, carried out in a wide temperature range, revealed that Ag1− x Li x NbO3, for x ≤0.05, undergoes the same complex sequence of phase transitions as AgNbO3 . On the other hand, for x >0.06, the temperature dependence of dielectric permittivity exhibits only two maxima, related to transitions from the ferroelectric R phase to the antiferroelectric M phase and followed by the paraelectric O phase. The dielectric results obtained confirm the existence of the morphotropic phase boundary.